2017
DOI: 10.3390/ma10030301
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Fracture Toughness in Epoxy Nanocomposites through Chemical Hybridization of Carbon Nanotubes and Alumina

Abstract: The current study investigated the effect of adding a carbon nanotube–alumina (CNT–Al2O3) hybrid on the fracture toughness of epoxy nanocomposites. The CNT–Al2O3 hybrid was synthesised by growing CNTs on Al2O3 particles via the chemical vapour deposition method. The CNTs were strongly attached onto the Al2O3 particles, which served to transport and disperse the CNTs homogenously, and to prevent agglomeration in the CNTs. The experimental results demonstrated that the CNT–Al2O3 hybrid-filled epoxy nanocomposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Generally, the main potential of graphene and carbon nanotubes as a structural element in epoxy nanocomposites are known for their ability to improve fracture toughness. As mention earlier, previous studies have reported that the incorporation of graphene and carbon nanotubes into epoxy matrix could lead to the enhancement of fracture toughness . In this study, the three‐point bend specimen of neat epoxy, Epoxy/SLG and Epoxy/SWCNT were used to determine mode 1 fracture toughness, K 1C .…”
Section: Resultssupporting
confidence: 55%
“…Generally, the main potential of graphene and carbon nanotubes as a structural element in epoxy nanocomposites are known for their ability to improve fracture toughness. As mention earlier, previous studies have reported that the incorporation of graphene and carbon nanotubes into epoxy matrix could lead to the enhancement of fracture toughness . In this study, the three‐point bend specimen of neat epoxy, Epoxy/SLG and Epoxy/SWCNT were used to determine mode 1 fracture toughness, K 1C .…”
Section: Resultssupporting
confidence: 55%
“…In addition, river lines are also present in such kind of material, as seen in Fig. . Most of the river lines had an inclination related to the crack propagation direction (white arrow in Fig.…”
Section: Toughening Mechanismsmentioning
confidence: 96%
“…For the 50 and 500 nm size particles, the static fracture toughness is higher than dynamic and interestingly the dynamic fracture toughness reduces with increase in volume fraction. Zakaria et al synthesized CNT–Al2O3 hybrid compounds by growing CNTs on the Al2O3 particles via CVD and then analyzed the improvement in toughness by incorporating these materials into the epoxy matrix. They also compared the properties of these hybrid composites with the composites prepared by mixing nano alumina and CNT particles in the epoxy matrix.…”
Section: Nanofiller Toughened Epoxy Compositesmentioning
confidence: 99%